Pengaruh Pelaksanaan Pendidikan Moral Kristen Dalam Keluarga dan Interaksi Sosial Terhadap Praktek Menghargai Orang Lain Remaja - Silaban, Angga Andika (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2023)
This study aims to determine the effect of implementing Christian moral education in the family and social interaction on the practice of respecting other people's youth GKPI Duma Sirisisi Kec. Doloksanggul, with the hypothesis: 1). There is a positive and significant influence between the implementation of Christian moral education in the family and social interaction on the practice of respecting others. This research uses descriptive and inferential quantitative methods. The research population consisted of 35 people with a sample of 35 people. The research instrument was a closed questionnaire, which was compiled based on the research variable indicators. Questionnaire trials were conducted on 30 people who were not research samples, and had been tested with validity and reliability tests. The hypothesis above is accepted for truth with the data: 1). There is a positive and significant influence between the implementation of Christian moral education in the family on the practice of respecting others by 46.51% with FcountFtable, namely 28.434.13. 2). There is a positive and significant influence between social interaction on the practice of respecting others by 37.33% with FcountFtable, namely 19.43 4.13. 3). There is a positive and significant influence between the implementation of Christian moral education in the family and social interaction together on the practice of respecting others by 54.16% with FcountFtable, namely 18.933.30, with the regression equation thus H0 is rejected and Ha is accepted. Based on the results of the study, it can be concluded that there is a positive influence on the implementation of Christian moral education in the family and social interaction on the practice of respecting other people. GKPI Duma Sirisisi Kec. Doloksanggul individually or together because it has been tested empirically. The implication: If you are going to improve the practice of respecting others, parents must apply moral education and teenagers interact with the environment